A precariedade do trabalho sob o olhar das pessoas em situação de rua de Fortaleza - Santos, Isabel Cristina Monteiro dos (2024)
The homeless population is inserted into the work environment after fragmenting various labor alternatives, and this ends up generating distinction, resulting in precarious alternatives for survival for those living in extreme social vulnerability. The starting question addresses how homeless people fit into the work environment given the precariousness of work in the city of Fortaleza-CE? The general objective of this research is to analyze the precariousness of work as a possibility of insertion into the work environment for homeless people in Fortaleza. The specific objectives were to understand the insertion of homeless people in Fortaleza into the work environment, analyze the meanings attributed by homeless people in Fortaleza to work and identify strategies for coping with homelessness through work. Regarding the methodology, it is qualitative. Six homeless people from Fortaleza were interviewed and who attended the Centro de Referência Especializado em Pessoas em Situação de Rua (Centro Pop Centro) and the Grupo Espírita Casa da Sopa. The content analysis method was used to systematize the interview transcriptions with the help of Atlas T.I, based on the categories: reference point; homelessness; work; work types; precariousness and coping strategies. The main results were: the homeless population has a chronology on the streets, those who carry out work activities are included in services to meet their basic needs, as the income earned is not enough; it is noted that these people carry out precarious jobs such as: self-employment, odd jobs and volunteering and have no security. Finally, it is understood that work is seen for these people as a way off the streets and makes them feel like they belong to social life.